Antigenic Characterization of Street Rabies Virus Isolates from Nigeria Using Monoclonal-Antibodies - Umoh, J. U.; Cox, James H.; Schneider, Lothar (Journal of Veterinary Medicine, Series B, 1990)
Twenty isolates of street rabies virus were recovered in mouse neutroblastoma cells from 84 rabies suspect brain specimens from Nigeria dogs and a cat. They were characterized with the Tübingen monoclonal antibody panels directed against nucleocapsid and glycoprotein antigens. Antigenic variatons were detected both with antinucleocapsid (anti‐NC) and antiglycoprotein (anti‐GP) monoclonal antibodies (mabs). One isolate reacted positively with anti‐NC mab P41 which hitherto has been known to react positively with polar rabies. Another isolate did not react with anti‐NC mab 187.5; a reaction normally seen with ERA/SAD strains of rabies virus. With anti‐GP mabs it was possible to group the isolates by their area of origin. Isolates from Plateau State were not neutralized by anti‐GP mabs ERA 543 and P44.7.2. The isolates studied had glycoprotein antigenic patterns different from the pattern for low egg passage (LEP) Flury strain vaccine virus used in Nigeria for immunization of dogs. Aus Gehirnproben von 84 Hunden und einer Katze aus Nigeria, in denen Tollwut‐Straßenvirus vermutet wurde, konnten 20 Isolate an Maus‐Neuroblastomzellen angepaßt werden. Diese wurden mit den in Tübingen verwendeten monoklonalen Antikörpern (MKA) auf Nukleokapsid‐ und Glykoproteinantigene charakterisiert. Antigenunterschiede gab es mit Antinukleokapsid‐MKA und Antiglykoprotein‐MKA. Ein Isolat reagierte positiv mit Antinukleokapsid‐MKA P41, das üblicher‐weise mit Isolaten der arktischen Tollwut positiv reagiert. Ein anderes Isolat reagierte nicht mit Antinukleokapsid‐MKA 187.5, eine Reaktion, die man üblicherweise bei ERA/SAD‐Stämmen des Tollwutvirus sieht. Mit Antiglykoprotein‐MKA war es möglich, die Isolate nach der geographischen Herkunft einzuordnen. Isolate vom Plateau State (Nigeria) wurden von den Antiglykoprotein‐MKA ERA 543 und P44.7.2 nicht neutralisiert. Die untersuchten Isolate hatten ein Glykoproteinantigenmuster, das unterschiedlich war vom Muster für den Low Egg Passage (LEP) Flury‐Stamm, der in Nigeria zur Herstellung von ...